EXPERIMENTAL RESEARCHES OF FINE-GRAINED CONCRETE CONSTRUCTIONS - S V Klyuyev (Structural Mechanics of Engineering Constructions and Buildings, 2011)
Acute questions of polypropylene using for disperse-reinforced fine-grained concrete are considered. Researchers of steel fibber concrete patterns based on astringent material are held